Movement as a critical concept in model generation to attain wholeness - Charlene Downing; Marie Poggenpoel; Chris Myburgh (AOSIS, 2017)
Movement is an integral aspect of daily living. Movement allows the human being to express, find meaning and reflect a part or the whole of the unfolding of the stories of their lives. The essence of the dialogue is the movement towards caring and healing between the professional nurse and the individual.The purpose of this research is to develop, describe, evaluate and provide guidelines for the operationalisation of a model as a framework of reference for nursing to facilitate the individual faced with mental health challenges as an integral part of wholeness. A model was generated to facilitate the engagement of self through movement, which contributes to and manifests in a mindful way of living to promote mental health as an integral part of wholeness. The findings of the study are applicable to the world of nursing practice, nursing education and research.